Individual Exploration to Organizational Commitment or Withdrawal - Stumpf, Stephen A.; Hartman, Karen (Academy of Management Journal, 1984)
The organizational commitment or withdrawal process was investigated for a sample of 85 individuals using a longitudinal research design and path analysis. Career exploration activity two months prior to entry predicted organizational entry and socialization variables, which in turn predicted early job attitudes and intentions. Intention to quit predicted subsequent exploration behavior and turnover.